2022
DOI: 10.1080/21645515.2022.2123201
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine confidence among people who use drugs: A cross-sectional survey

Abstract: Adult immunization coverage remains low in the US, particularly for people who use drugs (PWUD), a population that experiences a disproportionate burden of vaccine-preventable diseases. The extent of and characteristics associated with vaccine confidence (VC) held by PWUD is poorly understood. As VC strongly correlates with vaccine uptake, this cross-sectional study identifies mutable factors associated with VC and quantifies its relationship to immunization status within a highly vulnerable, underimmunized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
1
0
0
Order By: Relevance
“…Consistent with previous studies regarding COVID-19 and other vaccinations, our results demonstrated that PWUD were concerned about the speed of vaccine development, safety of use, side effects, usefulness, and experienced distrust toward healthcare and government agencies involved in vaccine distribution [ 26 31 , 43 ]. We found that many unvaccinated and partially vaccinated participants reported a lack of knowledge about the COVID-19 vaccine, which discouraged vaccine uptake and amplified already existing medical and government mistrust within this community.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies regarding COVID-19 and other vaccinations, our results demonstrated that PWUD were concerned about the speed of vaccine development, safety of use, side effects, usefulness, and experienced distrust toward healthcare and government agencies involved in vaccine distribution [ 26 31 , 43 ]. We found that many unvaccinated and partially vaccinated participants reported a lack of knowledge about the COVID-19 vaccine, which discouraged vaccine uptake and amplified already existing medical and government mistrust within this community.…”
Section: Discussionsupporting
confidence: 89%